Real-Time Monitoring of Knitting Machine Performance Using IoT and Machine Learning: Innovations and Applications (Journal of Fiber Bioengineering and Informatics, 2024)
Textile technologies are revolutionising with Industry 4.0. This research aims to introduce a novelreal-time monitoring system in the knitting sector using the Internet of Things and machine learningtechnologies to measure and display productivity precisely through an interactive dashboard. Sensorswere integrated into a circular knitting machine to track productivity and performance. A comparativestatistical analysis through three processing phases demonstrates the high accuracy and precision ofthe current system, as evidenced by minimum variance and error values. The t-test results validate anon-significant difference between actual and device-measured production. Thus, it enables real-timemonitoring, preventive maintenance, and cost-effective quality in knitting machines.